Integrative RNA-seq and ATAC-seq analysis unveils antioxidant defense mechanisms in salt-tolerant rice variety Pokkali - Qiaoyu Yang; Yutong Zheng; Xitao Li (BMC Plant Biology)
Abstract Background Salt stress is one of the most significant environmental challenges, severely impacting rice growth and yield. While different rice varieties exhibit varying levels of tolerance to salinity, Pokkali, a traditional salt-tolerant variety, stands out for its ability to thrive in saline conditions. Understanding the molecular and physiological mechanisms that underpin this tolerance is essential for breeding and developing rice varieties with enhanced resilience to salt stress. Methods In this study, we selected the salt-tolerant rice variety Pokkali and the salt-sensitive variety IR29 for a controlled saline stress experiment. Plants were subjected to a 150 mM NaCl treatment for 7 days, after which leaf samples were collected from both varieties. Antioxidant physiological parameters were measured, and RNA-seq and ATAC-seq analyses were conducted to explore gene expression and chromatin accessibility. Key genes identified through sequencing were validated using RT-qPCR. Results Under salt stress, Pokkali demonstrated strong tolerance and a higher antioxidant capacity compared to IR29, as evidenced by increased survival rates and fresh weight. Pokkali also showed elevated activity of antioxidant enzymes such as superoxide dismutase, peroxidase, and catalase, along with reduced accumulation of hydrogen peroxide. Transcriptomic and ATAC-seq analyses revealed that Pokkali’s upregulated genes were significantly enriched in pathways related to redox homeostasis. These genes were also involved in metabolic processes such as glycan biosynthesis, amino acid metabolism, carbohydrate metabolism, and energy production. Furthermore, ATAC-seq analysis indicated increased chromatin accessibility in the promoter regions of key antioxidant genes under salt stress in Pokkali, reflecting enhanced transcriptional activity. Four key antioxidant-related genes—MnSOD1, OsAPx7, OsGR1, and Osppc3—were identified and validated by qPCR, showing significant upregulation in Pokkali. ATAC-seq data further supported that these genes had increased promoter accessibility under salt stress, aligning with the RNA-seq findings. Conclusion This study underscores the critical role of antioxidant defense mechanisms in conferring salt tolerance in Pokkali. The identification of key genes involved in redox regulation provides valuable insights into the molecular basis of salt tolerance, offering potential targets for the genetic improvement of salt-sensitive rice varieties through breeding programs.